Tissue-engineered oral mucosa - Moharamzadeh, K.; Colley, H.; Murdoch, C.; Hearnden, V.; Chai, W.L.; Brook, I.M.; Thornhill, M.H.; MacNeil, S. (2012)
Advances in tissue engineering have permitted the three-dimensional (3D) reconstruction of human oral mucosa for various in vivo and in vitro applications. Tissue-engineered oral mucosa have been further optimized in recent years for clinical applications as a suitable graft material for intra-oral and extra-oral repair and treatment of soft-tissue defects. Novel 3D in vitro models of oral diseases such as cancer, Candida, and bacterial invasion have been developed as alternatives to animal models for investigation of disease phenomena, their progression, and treatment, including evaluation of drug delivery systems. The introduction of 3D oral mucosal reconstructs has had a significant impact on the approaches to biocompatibility evaluation of dental materials and oral healthcare products as well as the study of implant-soft tissue interfaces. This review article discusses the recent advances in tissue engineering and applications of tissue-engineered human oral mucosa.